Web reports: critically appraising online resources - Lapinsky, Stephen (BioMed Central, 2002)
The Internet is an invaluable resource for critical care clinicians. However, the search for useful Internet resources can be frustrating and time-consuming. In this issue, Critical Care launches a new section entitled 'Web Reports', which will regularly provide critical appraisal of Internet resources that may be of interest to critical care health care workers.